Gender, Sport and Development in Africa : Cross-cultural Perspectives on Patterns of Representations and Marginalization - Shehu, Jimoh (Book collections on Project MUSE., 2010)
To many young people, the term sport has an exhilarating ring; to many older persons, it signifies recreation and leisure. From colonial times, it has been viewed as a means of social control. Increasingly, it is being touted by governments and donor agencies as a self-evident tool of Africaís development. How accurate are these individual, romantic and moral notions of sport? In this volume, eleven African scholars offer insightful analyses of the complex ideological and structural dimensions of modern sport as a cultural institution. Drawing on various theories and cross-cultural data, the contributors to this volume highlight the various ways in which sport norms, policies, practices and representations pervasively interface with gender and other socially constructed categories of difference. They argue that sport is not only a site of competition and physical recreation, but also a crossroad where features of modern society such as hegemony, identities, democracy, technology, development and master statuses intertwine and bifurcate. As they point out in many ways, sport production, reproduction, distribution and consumption are relational, spatial and contextual and, therefore, do not pay off for men, women and other social groups equally. The authors draw attention to the structure and scope of efforts needed to transform the exclusionary and gendered nature of sport processes to make them adequate to the task of engendering Africaís development. Gender, Sport and Development in Africa is an immensely important contribution to current debates on the broader impacts of sport on society. It is an essential reading for students, policy-makers and others interested in perspectives that interrogate the grand narratives of sport as a neutral instrument of development in African countries.